Tourism Village Resilience And Adaptive Strategies Amid Dual Policy Shocks: Empirical Evidence From Community-Based Tourism In Indonesia - Hannif Andy Al Anshori; Muhammad Dzulkifli; Alfi Turni Aji Sulistyaningrum; Reza Permadi; Kasno Pamungkas; Awaludin Nugraha (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2026)
This research aims to examine the impact of budget efficiency and study tour restrictions on the performance and economic resilience of tourism villages in Indonesia. The research focuses on two major policy interventions: Presidential Instruction No. 1 of 2025 concerning budget efficiency and the West Java Governor’s Circular Letter restricting school-organized study tours—both of which have reshaped patterns of public spending and tourism demand. Employing a descriptive survey approach, data were collected from 85 tourism village managers across Indonesia through an online survey conducted in the first quarter of 2025. The findings reveal that 48.2% of respondents experienced booking cancellations and revenue declines, primarily from institutional and educational markets, while 64% identified limited local government program support as the main barrier to economic recovery. Despite these policy pressures, most tourism villages demonstrated adaptive resilience by engaging in digital promotion, product innovation, and market diversification. Moreover, there was a notable spatial shift in visitor origins from West Java and Yogyakarta to Central and East Java, indicating proactive market repositioning to mitigate policy-induced demand shocks. Conceptually, these findings demonstrate that community-based tourism (CBT) resilience is not merely a passive capacity to absorb regulatory shocks, but a dynamic, evolutionary process governed by community agency and digital agility. Theoretically, this study advances tourism governance literature by demonstrating how localized adaptations can decouple rural destinations from institutional market structural dependencies. Ultimately, it underscores the need for an evolutionary framework in tourism policy that balances centralized structural regulations with community-led socio-ecological adaptation. The research concludes that sustaining tourism village resilience requires integrated, participatory, and cross-sectoral policy coordination connecting education, tourism, and local governance.